Validation of real case solving (RCS) methodology as an efficient engineering learning tool - Aitor Goti; Tugce Akyazi; Alberto de la Calle; Aitor Oyarbide-Zubillaga; Elisabete Alberdi (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
In recent times, new learning methodologies known as student-based methodologies have been introduced to simplify the learning process for the students and facilitate the acquisition of skills for them. Among them, problem based learning (PBL) and project-based learning (PjBL) are widely used methods in the world of education. Real case solving (RCS) is a variant of the PBL where students solve real cases through the application of the PBL methodology. RCS seems to be a relevant approach for educators, but it has an apparently limited implementation degree at the academic level. This article presents the successful implementation of four different RCS approaches in the lecturing process in five different classes in the engineering degree of University of Deusto. The initiative has been analyzed both quantitative and qualitatively; the overall performance and success rate of the students were compared with the ones acquired from conventional teaching methods. The results were found to be promising, demonstrating a significantly better performance than the traditional teaching methodologies. The successful results encouraged the university to continue working further in this direction.
Keywords: 650; education; engineering; problem based learning; real case solving; simulation